ANALISA KINETIKA REAKSI PEMBENTUKAN KERAK CaCO 3 TRAKSI Vol. 17 No. 2 Desember 2017 -CaSO 4 DALAM PIPA BERALIRAN LAMINAR PADA SUHU 30 0 C DAN 40 C MENGGUNAKAN PERSAMAAN ARRHENIUS - Haryono Haryono (TRAKSI, 2017)
The crust is a hard pile of inorganic material especially on the heat transfersurface caused by deposition of mineral particles in water. Know the reaction rate constant and activation energy of CaCO3-CaSO4 scale formation with Arrhenius equation. The higher the temperature makes the crust more and more formed. At a temperature of 30 0C produces a crustal mass of 38.1 mg while at 40 0C the resulting crust mass is 58.5 mg. The higher the temperature makes the value of the reaction speed constant rising. At 30 0C the resulting reaction rate constant is 1,195 kJ.mg-1.C-1. While at a temperature of 40 0C yields a reaction rate constant of 3.737 kJ.mg-1.C-1. The activation energy in the CaCO3 crust formation reaction is 123.23 kJ. From SEM results between no additions and with the addition of cubical morphological forms with rombohedral and monoclinic crystal structures.Keywords: Crust, CaCO3, CsSO4, SEM